Patološka fiziologija akutnega in kroničnega popuščanja ledvic - Ribarič, Samo (Medicinski razgledi, 2005)
Renal injury can lead to acute (AKD) or chronic kidney disease (CKD). The presence, progress and distinction between AKD and CKD can be determined by monitoring serum creatinine and BUN values. Prerenal kidney failure is the most common form of AKD. AKD can be irreversible or, alternatively, can lead to a slow recovery of kidney function. Symptoms and signs of CKD often developslowly and depend on the percentage of functional nephrons. Individualscan remain asymptomatic until AKD is far advanced. Uremia develops during the final stage nf CICD. The development of signs and symptoms of uremia correlates well with BUN values.
Keywords: Ledvica, odpoved akutna; Kidney Failure, Acute; Physiopathology; Ledvica, odpoved kronična; Poliurija; Kidney Failure, Chronic; Polyuria; ledvice; fiziologija; ledvične bolezni; kronična ledvična odpoved; patofiziologija